The effect of nutrients on telomere length of fetal DNA: findings from the Mamma & Bambino cohort. (20th October 2021) - Magnano San Lio, R; Barchitta, M; Maugeri, A; La Rosa, MC; Caruso, M; Giunta, G; Panella, M; Cianci, A; Agodi, A
Abstract: Background: In the first 1, 000 days of life, from conception to two years of age, a variety of exposures could shape children's health. Identifying what maternal factors early affect biological aging in children represents a major public health mission. The present study aims to assess the relationship between maternal intake of nutrients in early pregnancy and telomere length of cell-free circulating fetal DNA (cffDNA) from amniotic fluid. Methods: We used data and samples from the ongoing prospective "Mamma & Bambino" study, which recruits mother-child pairs from Catania (Italy) at the first prenatal visit. Maternal nutrient intakes were assessed using a Food Frequency Questionnaire referred to one-month prior the recruitment. Relative telomere length of cffDNA was assessed by real-time polymerase chain reaction, among those women who underwent amniocentesis. Results: The study included 174 mother-child pairs (mean maternal age = 35.7 years) recruited from 4th to 20th gestational week. The intakes of iron, vitamin B1, and magnesium were positively correlated with relative telomere length (p-values based on Spearman's test = 0.05). However, only the intake of magnesium was positively associated with relative telomere length (β = 0.002; SE = 0.001; p = 0.024), after applying a linear regression model which included maternal age, smoking, pregestational body mass index, and total energy intake. Magnesium deficiency was negatively associated with relative telomere length after adjusting for the same covariates (β = -0.467; SE = 0.176; p = 0.009). Conclusions: To our knowledge, this is the first evidence of a relationship between maternal nutrient intake and telomere length of cffDNA. The positive effect observed for magnesium is consistent with previous studies conducted in other settings. However, further efforts are needed to translate the transgenerational effect of maternal behaviors to effective public health strategies. Key messages: It is crucial to understand the early effect of maternal diet on biological aging in children. The intake of magnesium positively modulates telomere length, a promising marker of aging before birth.